Pancreatic cancer: advances in treatment, results and limitations - Hackert, Thilo; Büchler, Markus W. (Digestive diseases, 2013)
Pancreatic cancer remains a therapeutic challenge. Surgery is the only treatment with the chance of cure. The aim of this review is to summarize the present state-of-the-art surgical procedures in pancreatic cancer. Methods: The current literature was reviewed with regard to surgical approaches in pancreatic cancer. A focus was put on high-quality studies, reviews, systematic reviews and meta-analyses as well as recruiting studies highlighting innovative approaches. Results: Today, standard resections can be performed with mortality rates below 5% in specialized high-volume institutions. Extended approaches for locally advanced cancer are technically feasible, including venous resections, multivisceral resections and recurrence surgery. They can be carried out without increased morbidity and mortality, are not compromised by higher R1 or N+ rates, and can improve survival. Arterial tumor invasion is still regarded controversially and is oncologically questionable. All surgical approaches should be part of interdisciplinary multimodal treatment concepts to improve the patients' prognosis. Conclusion: Surgery is the backbone of pancreatic cancer treatment in localized disease. Extended approaches are feasible in centers and show - except for arterial resections - good long-term outcome. Interdisciplinary therapy is an essential supplementation of all surgical approaches.